Pengaruh Transfer Pricing, Kepemilikan Institusional dan Kompensasi Rugi Fiskal terhadap Tax Avoidance Studi Kasus Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Puja Gusti Wardana; Ardan Gani Asalam (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This research was conducted to determine whether transfer pricing, institutional ownership and compensation for losses have an effect on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. This study uses descriptive statistical analysis methods and panel data regression analysis using Eviews software version 10. The sampling in this study was using purposive sampling technique so that 33 companies were obtained with an observation period of 5 (five) years. From the research conducted, it is revealed that transfer pricing, institutional ownership and fiscal loss compensation have a simultaneous effect on tax avoidance. While partially, only institutional ownership variables have a positive effect on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019.